Impact of Rosuvastatin Treatment on HDL-Induced PKC-βII and eNOS Phosphorylation in Endothelial Cells and Its Relation to Flow-Mediated Dilatation in Patients with Chronic Heart Failure - Ephraim B. Winzer; Pauline Gaida; Robert Höllriegel; Tina Fischer; Axel Linke; Gerhard Schuler; Volker Adams; Sandra Erbs (Cardiology Research and Practice)
Background. Endothelial function is impaired in chronic heart failure (CHF). Statins upregulate endothelial NO synthase (eNOS) and improve endothelial function. Recent studies demonstrated that HDL stimulates NO production due to eNOS phosphorylation at Ser1177, dephosphorylation at Thr495, and diminished phosphorylation of PKC-βII at Ser660. The aim of this study was to elucidate the impact of rosuvastatin on HDL mediated eNOS and PKC-βII phosphorylation and its relation to endothelial function. Methods. 18 CHF patients were randomized to 12 weeks of rosuvastatin or placebo. At baseline, 12 weeks, and 4 weeks after treatment cessation we determined lipid levels and isolated HDL. Human aortic endothelial cells (HAEC) were incubated with isolated HDL and phosphorylation of eNOS and PKC-βII was evaluated. Flow-mediated dilatation (FMD) was measured at the radial artery. Results. Rosuvastatin improved FMD significantly. This effect was blunted after treatment cessation. LDL plasma levels were reduced after rosuvastatin treatment whereas drug withdrawal resulted in significant increase. HDL levels remained unaffected. Incubation of HAEC with HDL had no impact on phosphorylation of eNOS or PKC-βII. Conclusion. HDL mediated eNOS and PKC-βII phosphorylation levels in endothelial cells do not change with rosuvastatin in CHF patients and do not mediate the marked improvement in endothelial function.